2007
DOI: 10.1007/s00405-007-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of allergic fungal sinusitis with intracranial spread

Abstract: Allergic fungal sinusitis (AFS) is a form of paranasal nasal disease if not managed early often involves bone destruction and extension into the orbit and anterior skull base. We present our study of patients with AFS with intracranial, exdradural extension. This study includes our experience of 26 patients with the histological and immunological diagnosis of AFS based on findings of branching septate fungi interspersed with eosinophilic mucin and Charcot-Leyden crystals without fungal invasion of soft tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
(53 reference statements)
0
17
1
Order By: Relevance
“…This observation was contrary to the observation made by Ikram et al 18 where the large series of chronic sinusitis patients were not found to have residual disease.…”
Section: Preoperativecontrasting
confidence: 99%
“…This observation was contrary to the observation made by Ikram et al 18 where the large series of chronic sinusitis patients were not found to have residual disease.…”
Section: Preoperativecontrasting
confidence: 99%
“…None required a craniotomy. Postoperatively, all patients received oral steroid therapy for one month (0.5 mg/kg) and remained disease-free for a period of up to 5 years [ 32 ]. In our case, there were no irreversible complications except a recurrent polyp.…”
Section: Discussionmentioning
confidence: 99%
“…None required craniotomy. Postoperatively, all patients received oral steroid therapy for 1 month (0.5 mg/kg), and remained disease free for a period of up to 5 years [45].…”
Section: Afrs With Intracranial Extensionmentioning
confidence: 99%